PENGARUH ROLE CONFLICT TERHADAP KEPUASAN KERJA PADA PERAWAT RUMAH SAKIT TINGKAT III dr. REKSODIWIRYO PADANG DENGAN WORK FAMILY CONFLICT SEBAGAI VARIABEL MEDIASI - Fitria Hariningsih; Rini Sarianti; Thamrin Thamrin (Jurnal Ecogen, 2019)
This study aims to determine the effect of Role Conflict on nurse job satisfaction with work family conflict as a mediating variable. The variables of this study include role conflict, job satisfaction and work family conflict. This research is a quantitative explanatory study. This study reaches out to inpatient nurses who are married RS Level III Dr. Reksodiwiryo Padang with a total sample of 70 nurses. The sample was obtained by the total sampling method. Data was obtained directly through respondents using a questionnaire. Data analysis includes descriptive analysis and inductive analysis which is used using SPSS.16. this study showed role conflict had a positive and significant effect on work family conflict, work family conflict had a negative and significant effect on job satisfaction and role conflict had a significant negative effect on nurse job satisfaction through work family conflict as a madiation variable. Role conflict cannot directly influence work satisfaction but must work through conflict family.Keywords: Conflict Role, Job Satisfaction, Work Family Conflict